Machine Learning in Medical Imaging 4th International Workshop, MLMI 2013, Held in Conjunction with MICCAI 2013, Nagoya, Japan, September 22, 2013, Proceedings - Wu, Guorong; Zhang, Daoqiang; Shen, Dinggang; Yan, Pingkun; Suzuki, Kenji; Wang, Fei (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2013)
This book constitutes the refereed proceedings of the 4th International Workshop on Machine Learning in Medical Imaging, MLMI 2013, held in conjunction with the International Conference on Medical Image Computing and Computer Assisted Intervention, MICCAI 2013, in Nagoya, Japan, in September 2013. The 32 contributions included in this volume were carefully reviewed and selected from 57 submissions. They focus on major trends and challenges in the area of machine learning in medical imaging and aim to identify new cutting-edge techniques and their use in medical imaging.